Dissemination Model for Critical Governments Information - Osaimi, Najd Al; Alghowinem, Sharifa (International Journal of Engineering and Technology, 2018)
Sharing information would not only raise awareness and increase knowledge, but could also save lives. Occasionally, governments need to provide critical information to citizens accurately and in a timely manner. There are different information dissemination channels such as: Television, Radio, SMS and Social Media. However, these channels have several limitations. A dissemination approach is needed that intelligently target specific citizens with critical information that concern them from trusted sources on time. In this research, we propose a dissemination model that addresses these issues and utilizes the needed features. Comparing several dissemination architectures, the proposed model is an enhanced architecture designed based on publish/subscribe. The study proposed a novel idea of information dissemination by integrating many trusted sources in a unified source that can be accessed by the stakeholders at any time. The study would be a building block for an official information dissemination system in Saudi Arabia.